ChemInform Abstract: Diastereo‐ and Enantioselective Nitro‐Mannich Reaction of α‐Substituted Nitroacetates to N‐Phosphoryl Imines Catalyzed by cinchona Alkaloid Thiourea Organocatalysts. Issue 36 (15th August 2013) - Fan, Weidong; Kong, Shasha; Cai, Yan; Wu, Guiping; Miao, Zhiwei
Abstract The presented method is highly tolerable to functionalized N‐phosphoryl imines and provides a reliable synthetic route to the corresponding β‐nitro ethylphosphoramidates (III) with adjacent quaternary and tertiary chiral centers in high enantio‐ and diastereoselectivity.